Oncofertility care and influencing factors among cancer patients of reproductive age from Saudi Arabia - Abusanad, Atlal; Mokhtar, Aseel Mohamed A.; Aljehani, Saad Adel A.; Aljuhani, Khaild Fuad A.; Saleh, Khalid Abdullah A.; Alsubhi, Baraa Hameed; Hamdi, Raad Mohammed; Alzoriri, Ammar Dawood (Frontiers in Reproductive Health, 2022)
Abstract: Background: More cancer survivors and a greater burden of long-term side effects have resulted from rising cancer incidence, improved treatment modalities, and younger age at cancer diagnosis. Treatment- related Infertility (TRI) is a well-known sequelae. This study looked at current oncofertility support and fertility preservation (FP) in men and women of reproductive age with cancer in Saudi Arabia, where there is little knowledge on the subject. Method: A cross-sectional study included oncology patients of reproductive age from an academic hospital was conducted. Patients’ characteristics, cancer type, treatment modalities and assessment of oncofertility support data were collected and examined to assess oncofertility support and potentially influencing factors. Results: Our study included 135 patients (39.3 % males and 60.7 % females). Although 66.7 % believed they were fertile at the time of diagnosis, and more than half planned to have children in the future, Unfortunately, only 37.8 % have received fertility counseling , and only 17% have seen a fertility specialist. In male patients, the most common FP method was sperm cryopreservation (6.7 %), while the majority of both genders (87.4 %) did not use any FP method. Two-thirds of the patients are knowledgeable about TRI and FP methods. About half of the female patients (57.3 %) were advised about the possibility of post-treatment amenorrhea while only 8.1% of the whole cohort received psychological support. Conclusions: Despite patients' satisfactory knowledge of TRI and FP, oncologists infrequently referred their patients to a specialized fertility service. More than half of our patients expressed a desire to have children in the future, but this desire was impeded by limited oncofertility care and FP procedures. Several factors influenced the knowledge of TRI, fertility counseling and FP. It is critical to incorporate oncofertility into management planning as it has a significant impact on patients' quality of life.